4x-7=7(x-4)

Simple and best practice solution for 4x-7=7(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-7=7(x-4) equation:


Simplifying
4x + -7 = 7(x + -4)

Reorder the terms:
-7 + 4x = 7(x + -4)

Reorder the terms:
-7 + 4x = 7(-4 + x)
-7 + 4x = (-4 * 7 + x * 7)
-7 + 4x = (-28 + 7x)

Solving
-7 + 4x = -28 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-7 + 4x + -7x = -28 + 7x + -7x

Combine like terms: 4x + -7x = -3x
-7 + -3x = -28 + 7x + -7x

Combine like terms: 7x + -7x = 0
-7 + -3x = -28 + 0
-7 + -3x = -28

Add '7' to each side of the equation.
-7 + 7 + -3x = -28 + 7

Combine like terms: -7 + 7 = 0
0 + -3x = -28 + 7
-3x = -28 + 7

Combine like terms: -28 + 7 = -21
-3x = -21

Divide each side by '-3'.
x = 7

Simplifying
x = 7

See similar equations:

| M^(2/5)*m^(1/5) | | F(x)=8x^2-10x+2 | | 2y-x-7=0 | | 4(2p+4)=40 | | 4t^2=12t-9 | | x-(.65x)=24.5 | | 10(x+3)=120 | | -4x+9=2x+57 | | x+62=57 | | 53+x=50 | | -8x+1=4x+9 | | 5(x+1)=6x+8 | | 5(x-1)=6x+8 | | 7/2x-11/2=17/2 | | 1.3=x^2+0.3 | | 9+3(x-2)=9-4(x-9) | | 1.4q-6.1q+1.4=-26.8 | | 2(x+2)+x=2(x+1)+1 | | 1.4q-6.1+1.4=-26.8 | | 9+2cosx=10 | | r=Ct+a | | m^2-7.5=92.5 | | 7/5y=26/15 | | ((x-3)/6)=2-x | | 3+7x^2+10=0 | | 7/5z-38/45=53/45 | | x-3/6=2-x | | 52/51/91/34 | | -16x^2+14x+13.5=5 | | -(1/2)=x^-2 | | (X-9)(x^2+5x+6)=0 | | 52/51/91:34 |

Equations solver categories